2013
DOI: 10.1158/1541-7786.mcr-13-0101-t
|View full text |Cite
|
Sign up to set email alerts
|

Tpl2 Kinase Impacts Tumor Growth and Metastasis of Clear Cell Renal Cell Carcinoma

Abstract: Due to the innate high metastatic ability of renal cell carcinoma (RCC), many patients with RCC experience local or systemic relapses after surgical resection. A deeper understanding of the molecular pathogenesis underlying advanced RCC is essential for novel innovative therapeutics. Tumor progression locus 2 (Tpl2), upregulated in various tumor types, has been reported to be associated with oncogenesis and metastatic progression via activation of the MAPK signaling pathway. Herein, the relevance of Tpl2 in tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…An in vitro study [107] showed that the suppression of MAPK pathways impaired human ccRCC cells' proliferation, clonogenicity, anoikis resistance, migration, and invasion capabilities. Phosphorylated ERK1/2 expression is significantly upregulated in renal clear cell carcinoma when compared to normal cells, in relation to the pathological grade and clinical stage of ccRCC [108].…”
Section: Renal Tumorigenesismentioning
confidence: 99%
“…An in vitro study [107] showed that the suppression of MAPK pathways impaired human ccRCC cells' proliferation, clonogenicity, anoikis resistance, migration, and invasion capabilities. Phosphorylated ERK1/2 expression is significantly upregulated in renal clear cell carcinoma when compared to normal cells, in relation to the pathological grade and clinical stage of ccRCC [108].…”
Section: Renal Tumorigenesismentioning
confidence: 99%
“…57 To test the hypothesis that TPL2 is essential for MAM activation and myeloma progression, we crossed Tpl2 2/2 animals 41 to the genetically engineered myeloma model, Vk*MYC. 58,59 Following its initial discovery as an oncogene, 60 Tpl2 has been shown to variably act as a tumor promoter or suppressor gene in various models of solid tumors, [61][62][63][64][65][66][67][68][69][70][71] Figure 4C). By contrast, the rates of apoptosis (cleaved caspase 3 positivity) in CD138 1 cells from tumor-matched animals were low and not significantly different between the 2 genotypes ( Figure 4D).…”
Section: Tpl2 a "Druggable" Map3kinase Downstream Of Tlrs Controls mentioning
confidence: 99%
“…Therefore, anoikis resistance is critical for tumor metastasis. Previous research has reported certain factors that modulate anoikis sensitivity and resistance in ccRCC, including histone deacetylase inhibitors (18), tumor progression locus 2 kinase (19), and HMGA1 (20). Further mechanisms of anoikis sensitivity and resistance in ccRCC remain unknown.…”
Section: Discussionmentioning
confidence: 99%